Digitalisasi Hasil Produksi UMKM Bancar Purbalingga untuk Mengoptimalkan Kegiatan Pemasaran Produk Makanan Ringan (Snack) - Muhammad Hery Santoso; Mutiasari Mutiasari; Herni Utami Rahmawati; Nurul Hasanah; Guntoro Guntoro (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
MSMEs are able to drive the economy and lure other sectors to grow, develop and reduce unemployment and poverty. This sector can absorb a large enough workforce and provide opportunities for MSMEs to develop and be able to compete with other companies. However, since 2020, when the Covid 19 pandemic occurred in Indonesia, the MSME sector has suffered a severe blow and many have even gone out of business due to restrictions on community movements or PPKM. In this post-pandemic situation, the community service team is trying to help MSMEs by conducting business training and mentoring so they can rise from adversity. The partners for this community service activity are MSME actors in snacks in the form of egg rolls, chips, cheese macaroni, shredded and nastar in Bancar Purbalingga Village whose products are still marketed in a limited manner within the Banyumas residency. So far, marketing activities have been carried out by word of mouth and placed in customer stores, making it difficult to increase sales and develop their business. Methods for implementing community service include (1) situation analysis and identification of partners' problems, (2) determining problem solutions and activity achievement targets, and (3) activity evaluation. The solution offered is to increase marketing activities which have an impact on increasing business productivity and sales turnover by implementing digitization of MSME products. Conduct training and mentorship to partners regarding the use of websites to promote products digitally. The results of this activity are expected to (1) increase partners' understanding and knowledge regarding the importance of product digitization for more efficient marketing, (2) have a digital product catalog (3) increase the reach of promotions because they are carried out via the internet and social media networks.